Kesesuaian Wacana dalam JawaPos.com dengan Struktur Teks Eksposisi - Salma Rosita Nuringtyas; Septina Sulistyaningrum (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This research aims to describe the conformity of the discourse in JawaPos.com with exposition text structure material. The research method used is qualitative descriptive research. The data source for this research comes from the online mass media JawaPos.com. The data taken was in the form of fifteen exposition discourses in the January-February 2025 edition of JawaPos.com. The data collection technique used in this research was data collection by observation, documentation, and note-taking. The data analysis technique in this research uses the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The research results showed that of the fifteen exposition discourses analyzed, there were two discourses that did not match the structure of the exposition text. Thirteen other expository discourses have a complete and appropriate expository text structure, consisting of a thesis, argumentation and reaffirmation.